Organizational Social Capital: Ties Between HRD, Employee Voice, and CEOs. (June 2018) - Cumberland, Denise M.; Alagaraja, Meera; Shuck, Brad; Kerrick, Sharon A.
Growing employee voice increases the likelihood that employees will engage in discretionary efforts to share potentially useful information, express opinions, or concerns about work-related issues to their supervisors and other leaders in the organization. We develop a conceptual model and a series of propositions to examine and analyze the underlying mechanisms that enhance employee voice. Specifically, we identify linkages and connections between human resource development (HRD) practices, organizational social capital (OSC), and the role of CEOs as facilitating environmental or situational mechanisms that have implications on voice behavior. HRD can play a key role in helping employees foster social capital, leading to employee voice in the organization. When CEOs extend their existing internal social networks, and engage in conversations with workers, this dialogue serves as a visible artifact and reverberates across the organization. Our propositions move beyond framing employee-related voice outcomes as a result of either HRD practices or CEO influence. Rather, we postulate an outcome of their interdependent interactions. Implications for HRD research and practice are discussed.